Timing of first sexual intercourse: the role of social control, social learning, and problem behavior. - Crockett, Lisa J.; Bingham, C. Raymond; Chopak, Joanne S. (Journal of Youth & Adolescence, 1996)
Prior research has pointed to several distinct processes that may affect the timing of first intercourse among adolescents. In the present study, the role of six hypothesized processes was assessed in a sample of 289 rural adolescent boys and girls. Results support the importance of family socialization and problem behavior for both sexes, the role of biological factors for boys, and the role of social control processes for girls. Two other hypothesized influences—social class and poor psychosocial adjustment—were not supported in either gender. These results indicate that multiple processes influence the timing of first intercourse; thus, they underscore the need for eclectic predictive models that incorporate the multiplicity of influences. Reprinted by permission of the publisher.